2014
DOI: 10.1016/j.ssc.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of α-Fe upon the introduction of H, He, C, and N

Abstract: The effects of impurities of H, He, C, and N in α-Fe are investigated in terms of electronic structures using the density functional theory. Calculations reveal that H and He are stable at the T-site while C and N are stable at the O-site within α-Fe. The local strain field by H, He, C, and N in α-Fe cause structural elongation. Furthermore, the decrease of magnetic moment of Fe upon the introduction of C and N are found where the charge transfer is responsible. H, He, C, and N affect the electronic structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…The incorporation of desired impurities (or dopants) into the bulk has been studied extensively to modify or achieve desired bulk properties. In contrast, the fundamental understanding on the reversed process, that is, removal of impurities, is very limited. Macroscopically speaking, the removal of impurities from a material is usually time-consuming, energy intensive, and very costly.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of desired impurities (or dopants) into the bulk has been studied extensively to modify or achieve desired bulk properties. In contrast, the fundamental understanding on the reversed process, that is, removal of impurities, is very limited. Macroscopically speaking, the removal of impurities from a material is usually time-consuming, energy intensive, and very costly.…”
Section: Introductionmentioning
confidence: 99%
“…C and N atoms are seen to be stable at the octahedral site of Fe [11]. The diffusion barrier of C and N is reported to be greatly affected by the introduction of a vacancy into Fe [9].…”
Section: Introductionmentioning
confidence: 97%
“…The He atom is calculated to be stable at the tetrahedral site in Fe without a vacancy [11]. He is dissolved in endothermic matter in Fe without vacancy; therefore, He tends to diffuse easily due to the stress coming from the surrounding Fe atom.…”
Section: Introductionmentioning
confidence: 99%
“…9−11 In general, noble gases have low solubility, making the defect site behave as a trapping site. 12 However, the location and the role of noble gases at the metal/ oxide interface are not well understood, thereby making it difficult to determine whether noble gases stay at the interface or grow toward the metal or oxide sites.…”
mentioning
confidence: 99%
“…The metal/oxide interface in structural materials has been extensively investigated as it plays a key role for the thermal stability and mechanical strength of oxide dispersed metal. In addition, the presence of noble gases at such interfaces generates scientific and engineering interest as changes in the properties of these materials could be a result of noble gases at the interfaces. In particular, He and Ar gases are two common noble gases seen in metal/oxide interfaces where He atoms are induced by transmutation reactions and Ar atoms are introduced during material processing under fully saturated Ar gases in order to prevent oxidation. , Such noble gases are considered to play a crucial role in material fracturing and embrittlement where they generally form few nanometers of noble gas bubbles during the annealing process. , It is also reported that trapping He gases in Y–Ti based oxides is effective compared to trapping He in an Fe matrix in regards to preventing material fractures. In general, noble gases have low solubility, making the defect site behave as a trapping site . However, the location and the role of noble gases at the metal/oxide interface are not well understood, thereby making it difficult to determine whether noble gases stay at the interface or grow toward the metal or oxide sites.…”
mentioning
confidence: 99%